2021
DOI: 10.21203/rs.3.rs-886940/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Stage 1 Pilot Cohort Exploring the Use of EMDR Therapy as a Video-Conference Psychotherapy During Covid-19 – A Proof of Concept Study Utilising a Virtual Blind 2 Therapist Protocol

Abstract: Background The Covid-19 pandemic has had a major impact in the delivery of psychological treatment. Due to social distancing requirements provision moved to video-conferencing psychotherapy (VCP). There is a paucity of empirical data supporting the efficacy of EMDR therapy as a VCP. This stage 1 pilot study tested an EMDR therapy scripted protocol – Virtual Blind 2 Therapist (VB2T) as a VCP regarding fitness for purpose, distinctiveness, relevance, and efficiency. Methods Twenty-four participants were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Future exploration of the impact that previous childhood and adult adverse experiences can have on the development of future traumatic stress symptoms from a workplace incident is warranted. This would align with current research that has examined this factor, particularly as it relates to mental health (see, e.g., Farrell et al, 2022;Perri et al, 2021).…”
Section: Future Researchsupporting
confidence: 77%
See 1 more Smart Citation
“…Future exploration of the impact that previous childhood and adult adverse experiences can have on the development of future traumatic stress symptoms from a workplace incident is warranted. This would align with current research that has examined this factor, particularly as it relates to mental health (see, e.g., Farrell et al, 2022;Perri et al, 2021).…”
Section: Future Researchsupporting
confidence: 77%
“…Similarly, a comparison of seven sessions of CBT and R-TEP for ASD delivered via Skype found both interventions were effective in reducing anxiety, trauma, and depressive symptoms (Perri et al, 2021). A recent proof-of-concept study also found evidence that EMDR can be delivered via videoconference, however, concluded a clinical trial was warranted (Farrell et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study investigated the efficacy of EMDR therapy as a videoconferencing psychotherapy in 24 frontline mental health workers, exploring the treatment effect on the core characteristics of the trauma memory, namely, subjective disturbance, belief systems, memory intensity, vividness, and levels of emotionality. These results suggested the potential clinical benefits of using the EMDR as a videoconference psychotherapy (Farrell et al, 2022).…”
Section: E Cacy Of Emdr Interventions On the Long-term Psychological ...mentioning
confidence: 73%